Smart Farming Using Artificial Immune System Algorithm and Image Processing - T. , Suman; G. , Srinivasa (International Journal of Psychosocial Rehabilitation, 2020)
For any developing country like India, agriculture plays an important role and contributes a major part of the income to the country, so there is a need to grow and increase the yield effectively. In order to achieve the above objectives, one has to monitor the diseases starting from plantation to harvesting. In this paper we made an attempt to use Artificial Immune System(AIS) and image processing to (i) identify the diseases on fruits like grapes and apples and (ii) grade fruits. Disease identification aims at different features like color, texture, and shapes. Which are considered as feature vectors in this work. To extract color feature HSV histogram value concept is used; for texture wavelet transform method and for shape, morphology methods are used. After extracting the above-said features, we used the AIS algorithm as a classifier to classify the diseases, and it is observed that the color and morphology show better results than the texture. Grading of fruit aims at fruit segmentation, which calculates the healthy and infected portions of fruit. At the end we practically implemented the AIS algorithm, and results are obtained from MATLAB.